Effect of trilostane treatment on proteinuria secondary to spontaneous hypercortisolism in dogs - Filippo Tagliasacchi; Federico Fracassi; Maddalena Poli; Laura Dalla Tomba; Stefania Golinelli; Antonio Maria Tardo; Francesca Del Baldo (Journal of Veterinary Internal Medicine, 2026)
Abstract Background Proteinuria is reported in 68%-71% of dogs with spontaneous hypercortisolism (HC). The long-term effect of trilostane on HC-associated proteinuria remains poorly documented. Hypothesis/Objectives To evaluate the efficacy of trilostane on proteinuria in dogs with HC and identify potential clinical, anamnestic, and analytical differences between responders and nonresponders. Methods Retrospective longitudinal cohort study including dogs with proteinuric HC treated exclusively with trilostane. Clinical history and laboratory data at diagnosis (T0) were retrieved. When available, urine protein-to-creatinine ratio (UPC), disease clinical score (DCS), blood pressure (BP), and daily trilostane dosage (TD) were recorded at 30, 90, 180, and 365 days (T30, T90, T180, and T365) after treatment initiation. Dogs achieving a ≥ 50% UPC reduction or a final UPC < 0.5 were defined as “responders.” Results One hundred sixty dogs met inclusion criteria: 89% had pituitary-dependent HC and 10% adrenal-dependent HC. At diagnosis, 64% were proteinuric. A significant UPC reduction over time occurred (P = .0005; F(4,153.9) = 5.26), with statistically significant decreases at T90 (P = .020; difference, 1.093; 95% CI, 0.115-2.071), T180 (P = .031; difference, 1.122; 95% CI, 0.064-2.181), and T365 (P = .002; difference, 1.599; 95% CI, 0.436-2.761) compared to baseline. At the last follow-up, 76 dogs were evaluable; 48% were responders and had lower median DCS, BP, and TD (P = .029, P = .025, and P = .048, respectively) than nonresponders. Conclusions and Clinical Importance Trilostane induces a significant and sustained reduction in proteinuria in some dogs with spontaneous HC, evident from 3 months of treatment. Responders exhibit better control of hypertension and clinical signs despite lower TD. Nonresponders account for 52% of proteinuric dogs.